Freshwater Prawn Culture: The Farming of Macrobrachium Rosenbergii - New, Michael Bernard; Valenti, Wagner Cotroni [UNESP] (Wiley, 2007)
The farming of the freshwater prawn Macrobrachium rosenbergii has developed rapidly during recent years. Advances in techniques, and the huge expansion of world demand for this species, continue to stimulate the growth of a multi-million dollar industry. This landmark publication is a compendium of information on every aspect of the farming of M. rosenbergii. A comprehensive review of the status of freshwater prawn farming research, development and commercial practice, the book is intended to stimulate further advances in the knowledge and understanding of this important field. An extremely well-known and internationally-respected team of contributing authors have written cutting edge chapters covering all major aspects of the subject. Coverage includes biology, hatchery and grow-out culture systems, feeds and feeding, up-to-date information on the status of freshwater prawn farming around the world, post-harvest handling and processing, markets, and economics and business management. Further chapters are devoted to the culture of other prawn species, prawn capture fisheries and the sustainability of freshwater prawn culture. Contributions to the book have been brought together and edited by Michael New and Wagner Valenti, themselves widely known for their work in this area. The comprehensive information in Freshwater Prawn Culture will give an important commercial edge to anyone involved in the culture and trade of freshwater prawns. Readership should include prawn farm personnel, business managers and researchers, and invertebrate, freshwater and crustacean biologists. Copies of the book should be available on the shelves of all libraries in research establishments and universities where aquaculture and fisheries are studied and taught. Michael Bernard New, OBE is a Past-President of the World Aquaculture Society and President-Elect of the European Aquaculture Society; Wagner Cotroni Valenti is a Professor at the Aquaculture Center, São Paulo State University, Brazil.